Work Motivation, Organizational Commitment, and Transformational Leadership Style on Organizational Citizenship Behavior at PDAM Tirta Sembada Sleman - Rayi Gustu Mauren; Didik Subiyanto; Mohammad Ahyar Syafwan Lysander (Dinasti Review Publisher, 2026)
This study aims to analyze the effect of work motivation, organizational commitment, and transformational leadership style on organizational citizenship behavior (OCB) among employees of PDAM Tirta Sembada Sleman. This research uses a quantitative approach with a survey method by distributing questionnaires to 70 respondents. The data analysis techniques include validity and reliability tests, classical assumption tests, and hypothesis testing (t-test, F-test, and coefficient of determination). The results show that partially, work motivation does not have a significant effect on OCB, indicating that the level of employee motivation does not influence organizational citizenship behavior. Meanwhile, organizational commitment and transformational leadership style have a positive and significant effect on OCB. Simultaneously, all independent variables significantly affect OCB. The coefficient of determination (R²) value of 0.913 indicates that 91.3% of the variation in OCB can be explained by work motivation, organizational commitment, and transformational leadership style, while the remaining 8.7% is influenced by other factors outside the model.